Seasonal Resource Use Interactions between Wildlife and Livestock in Wildlife Sanctuaries in The Amboseli Ecosystem, Kenya - Mwasi, S. M.; Fisher, E. (Africa Environmental Review Journal, 2022)
Wildlife sanctuaries in the Amboseli ecosystem serve a dual purpose of wildlife dispersal areas and livestock grazing areas. It is therefore important to determine whether the presence of livestock affects wildlife resource use within the sanctuaries. Foot transects were conducted in Osupuko, Motikanju, Kilitome, Kimana, and Elerai-Rupet wildlife sanctuaries during early wet season 2010, late dry season 2010, and early wet season 2011 to assess temporal and spatial presence of wildlife and livestock. Jaccard’s similarity index, Pianka’s habitat use overlap index, Simpson’s diversity index, and Ivlev’s habitat selection indices were used to assess seasonal resource use interactions between wildlife and livestock. Overall, the presence of potential for competition through resource overlap indices did not dictate the same trends in wildlife diversity and habitat selection in any sanctuary. In three out of five wildlife sanctuaries there was a trend in which wildlife and livestock selected different habitats in the early wet season and similar habitats in late dry season. No trend was established among the sanctuaries in seasonal habitat selection. Livestock presence did not always negatively affect wildlife; indicating possible coexistence between the two. Seasonal grazing plans should be established in the sanctuaries to ensure coexistence of wildlife and livestock.